2011
DOI: 10.1586/ern.11.128
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of ramelteon in a double-blind, placebo-controlled, crossover study in Japanese patients with chronic primary insomnia

Abstract: The aim of this study was to evaluate the efficacy and safety of ramelteon 4, 8, 16 or 32 mg and placebo in Japanese patients with chronic insomnia using a randomized, double-blind, five-period crossover design. A total of 65 Japanese patients with chronic primary insomnia received ramelteon or placebo for two nights each in sleep laboratories. Changes in sleep parameters were assessed objectively by polysomnography and subjectively by postsleep questionnaires. Safety and tolerability was evaluated by assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…[118][119][120][121] The overall quality of evidence from these studies was downgraded to very low due to substantial heterogeneity across studies, imprecision and potential publication bias. The overall evidence for ramelteon 8 mg. was weakly in favor of its effectiveness for the treatment of sleep onset disturbance only.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[118][119][120][121] The overall quality of evidence from these studies was downgraded to very low due to substantial heterogeneity across studies, imprecision and potential publication bias. The overall evidence for ramelteon 8 mg. was weakly in favor of its effectiveness for the treatment of sleep onset disturbance only.…”
Section: Discussionmentioning
confidence: 99%
“…[118][119][120][121] Subjects in all studies demonstrated chronic primary insomnia with associated daytime complaints. All studies required mean objective LPS of > 20 min on two nights of PSG screening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations